Modifiable risk factors for cardiovascular diseases and quality of life among first-year nursing students - Marianna Sobral Lacerda; Marina Bertelli Rossi; Erika de Sá Vieira Abuchaim; Alba Lúcia Bottura Leite De Barros; Juliana de Lima Lopes (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To describe the risk factors for cardiovascular diseases and the quality of life of first-year college students. Methods A cross-sectional study conducted with first-year undergraduate nursing students attending a public university located in São Paulo, Brazil. The students completed nine questionnaires and the students'cervical and abdominal circumferences were measured along with their weight and height, blood pressure, lipid profile, and capillary blood glucose. Results 67 undergraduate students were included. Half of the students were physically inactive (73.1%), 7.5% reported smoking, 40.3% alcohol consumption, 25.4% overweight, and 16,4% increased total cholesterol. Depressive symptoms, anxiety, and stress were also reported, as well as excessive daytime sleepiness, risk of sleep apnea, and risky and harmful consumption of alcohol. As for the quality of life, the domains with the lowest scores were vitality and emotional aspects. Conclusion The most prevalent risk factors found in undergraduates were sedentary lifestyle, excessive daytime sleepiness and stress.